Aktualiasasi Pendidikan Islam dI Dalam Institusi-Institusi Madrasah terkemuka Abad Klasik - Muqoyyidin, Andik Wahyun (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2013)
Madrasa as an institution of Islamic education was an idea and a brilliant achievements in the fith century AH. With its uniqueness, during the Abbasiyah caliphate in Baghdad, madrassas became par - excellence educational institutions. After development and kuttab mosques, madrassas was growing very rapidly. Mirror at that time, the pattern of Islamic education has many variants, and almost all educational institutions when it received full support from the government in the fild of fiance. This was the cause of science and technology was growing rapidly. The madrassas which makes it very important function is the completeness of his room to study, known as muhadharah rooms and buildings associated with it,security for students and teachers. Similarly, in teaching and learning, teaching methods varied also be one of the aspects that are important for transferring knowledge and culture from a teacher to a student.Keywords : Islamic Education, Institution, Madrasa, Classic